Guantánamo und die Imperiale Autokratie - Saxe-Fernández, John (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
The Guantánamo prison operation is interpreted as a testing ground for a “new legal system”, and is analyzed, in the context of the war on terrorism at home (through a régime d´exception formalized in the Patriot Act) and abroad (through the “doctrine of pre-emptive war”), unleashed after the attacks in September 2001. It is further argued that this is a recent and extreme manifestation of the historical propensity of the US Executive branch (the Imperial Presidency), to usurp legislative and judicial functions and powers.